2007
DOI: 10.1088/0264-9381/24/18/r01
|View full text |Cite
|
Sign up to set email alerts
|

The asymptotic safety scenario in quantum gravity: an introduction

Abstract: The asymptotic safety scenario in quantum gravity is reviewed, according to which a renormalizable quantum theory of the gravitational field is feasible which reconciles asymptotically safe couplings with unitarity. All presently known evidence is surveyed: (a) from the 2+ǫ expansion, (b) from the perturbation theory of higher derivative gravity theories and a 'large N' expansion in the number of matter fields, (c) from the 2-Killing vector reduction, and (d) from truncated flow equations for the effective ave… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
283
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(296 citation statements)
references
References 164 publications
(340 reference statements)
5
283
0
Order By: Relevance
“…As an example we may cite the calculation of one-loop divergences in quantum gravity, where it can be shown that there exists a gauge choice for which the coefficient of the logarithmic divergences is zero [21]. Off-shell calculations of beta functions are common in the asymptotic safety approach to quantum gravity [22][23][24], and in such cases one may be interested in minimizing their dependence on the gauge choice.…”
Section: Jhep06(2016)115mentioning
confidence: 99%
“…As an example we may cite the calculation of one-loop divergences in quantum gravity, where it can be shown that there exists a gauge choice for which the coefficient of the logarithmic divergences is zero [21]. Off-shell calculations of beta functions are common in the asymptotic safety approach to quantum gravity [22][23][24], and in such cases one may be interested in minimizing their dependence on the gauge choice.…”
Section: Jhep06(2016)115mentioning
confidence: 99%
“…In the case of gravity, M. Reuter has pioneered the application of the Wetterich equation in [36]. Gravity-specific reviews of the asymptotic safety scenario and the application of the functional Renormalization Group can be found in, e.g., [71][72][73][74][75][76][77][78][79][80].…”
Section: Jhep04(2015)096mentioning
confidence: 99%
“…A subclass of these geometries is the piecewise linear geometries and a further subclass is the piecewise linear geometries defined by triangulations obtained by gluing together equilateral D-simplices such that they 1 The idea of a time foliation and the fact that there exists a related unitary time evolution are features which CDT shares with Hořava-Lifshitz gravity [6][7][8][9]. However, no spatial higher derivative terms are explicitly added to the action, like in Hořava-Lifshitz gravity, and it is possible that fixed points of the lattice theory can be identified with the non-trivial UV fixed points conjectured in the asymptotic safety scenario suggested by Weinberg [10] and investigated in [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Cdt and The Cdt Transfer Matrixmentioning
confidence: 99%